Meningkatkan keterlibatan siswa dalam pembelajaran olahraga: Peran modul elektronik, kreativitas guru, dan teknologi - Fantiro, Frendy Aru; Muzakki, Abdurrohman; Prakoso, Bayu Budi; Saputra, Setiya Yunus; Cendani Putri, Adelya Dwi (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Student engagement in physical education is essential for promoting active participation and effective learning. However, traditional teaching methods often struggle to maintain students’ interest and motivation. In response to technological advancements, this study explores how e-module development, teacher creativity, and technology use affect student engagement in sports education, with technology acting as a moderating variable. A quantitative approach was applied, involving 150 Indonesian high school students selected through purposive sampling, focusing on those actively participating in physical education and using e-modules. Data were collected via structured questionnaires measuring e-module development, teacher creativity, technology use, and student engagement. The data were analyzed using Partial Least Squares (PLS) 4.0. The results show that e-modules (β = 0.420, t = 7.746, p < 0.001), teacher creativity (β = 0.212, t = 3.668, p < 0.001), and technology (β = 0.200, t = 4.392, p < 0.001) significantly enhance student engagement. Moreover, technology strengthens the influence of both e-modules (β = 0.303, t = 5.908, p < 0.001) and teacher creativity (β = 0.214, t = 3.783, p < 0.001) on student engagement. These findings underscore the importance of integrating digital tools and creative teaching strategies in physical education. The study provides practical implications for educators aiming to boost student involvement through innovative, technology-supported instruction.